2015
DOI: 10.1111/jth.12885
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress‐independent binding of von Willebrand factor‐type 2B mutants p.R1306Q & p.V1316M to LRP1 explains their increased clearance

Abstract: Summary. Background: von Willebrand factor (VWF) is cleared in a shear stress-and macrophage-dependent manner by LRP1. von Willebrand disease (VWD)-type 2B mutants are endocytosed more efficiently than wildtype (wt)-VWF by macrophages. Objective: To investigate if VWD-type 2B mutations in the VWF A1-domain affect LRP1 binding and LRP1-dependent clearance. Methods: Recombinant Fc-tagged A1 domain (A1-Fc, A2-Fc, A3-Fc) and full-length VWF (wt or mutants thereof) were tested for binding to LRP1 or a recombinant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 30 publications
3
45
0
Order By: Relevance
“…Recent studies have shown that hepatic macrophages contribute to the clearance of full-length VWF. [21][22][23][24][25][26] To determine whether macrophages modulate A1-A2-A3 clearance in vivo, clearance studies were repeated following clodronate-induced macrophage depletion. In keeping with previous studies, clearance of full-length rVWF was significantly reduced following macrophage depletion ( Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have shown that hepatic macrophages contribute to the clearance of full-length VWF. [21][22][23][24][25][26] To determine whether macrophages modulate A1-A2-A3 clearance in vivo, clearance studies were repeated following clodronate-induced macrophage depletion. In keeping with previous studies, clearance of full-length rVWF was significantly reduced following macrophage depletion ( Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…2,14 However, accumulating data have demonstrated that macrophages play important roles in regulating VWF clearance in vivo, [21][22][23][24][25][26] and a number of putative macrophage receptors for VWF have been identified. 23,26,38 Critically, however, the specific regions of the VWF glycoprotein involved in modulating interactions with these different macrophage receptors have not been determined. In this study, using a series of in vivo and in vitro methodologies, we demonstrate that the A1-A2-A3 domains of VWF contain a receptor-recognition site important in mediating VWF binding to macrophages in vitro and in regulating VWF clearance by macrophages in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations